The ethics of infinite impact. Issue 1 (2nd January 2019) - Frodeman, Robert
ABSTRACT: Transhumanism, the research program devoted to increasing our physical and mental abilities and lengthening our lifespan, casts light on the term 'responsible innovation'. The goals of the transhumanists strike some as ludicrous, but the space between transhumanist pipedreams and the sober plans of the research community are essentially the same. This implies that talk of 'responsible innovation' is a cheat, for there is nothing responsible, or ethical, about a research culture whose goals are implicitly infinite.